Interface-enhanced and self-guided growth of 2D interlayer heterostructure wafers with vertically aligned Van Der Waals layers - Hu, Yi (2025)
2D heterostructures have garnered significant interest in the scientific community owing to their exceptional carrier transport properties and tunable band alignment. The fabrication of these heterostructures on a wafer scale is crucial for advancing industrial applications but remains particularly challenging for metals with low sulfidation activity, such as Hf. Herein, the one-pot method is developed for fabricating wafer-scale HfSe2/WSe2 interlayer heterostructures with vertically aligned van der Waals layers via interface-enhanced selenization and self-guided growth. By depositing a W layer (high sulfidation activity) over a Hf layer, followed by a one-pot selenization process, the chemical combination between Hf and Se atoms is enhanced through interfacial Se diffusion and confined lattice reaction. Moreover, the WSe2 layers grow perpendicular to the substrate and further guide the crystallization of the bottom HfSe2 layers. The resulting heterostructures, characterized by covalent bonds, demonstrate significant charge transfer, enhanced piezoelectricity, notable rectification effects, and Si-compatible transistor integration. This interface-enhanced selenization and self-guided growth pathway may provide valuable insights into the fabrication of covalently connected interlayer heterostructures involving metals with low sulfidation activity, as well as the development of high-density integrated circuits.